A systematic review and meta-analysis of the effectiveness of co-designed, in-person, mental health interventions for reducing anxiety and depression symptoms - Tamsin Greene Barker; Aoife O’Higgins; Peter Fonagy; Frances Gardner (2024)
Co-design is recommended in mental health fields and has been associated with improved intervention efficacy. Despite its growing popularity, syntheses of evidence on the effectiveness of co-designed interventions are scarce, and little is known about their impact on anxiety and depression. The purpose of this systematic review and meta-analysis was to consolidate evidence on the effectiveness of in-person, co-designed mental health interventions for reducing anxiety and depression symptoms. An exhaustive search was conducted across six electronic databases (PubMed, PsycINFO, Embase, CINAHL, CENTRAL, and ProQuest) and grey literature. Criteria for inclusion comprised studies utilizing randomized or quasi-randomized methods, implementing non-digital/in-person, co-designed interventions for mental health enhancement, and assessing anxiety and/or depression. Intervention impacts were evaluated using random-effects meta-analyses. The review identified 20 studies, with only three using the term 'co-design'. Other terminologies included 'co-developed' (n = 2), 'co-produced' (n = 2), and 'CBPR' (n = 11). Seventeen studies exhibited moderate risk of bias, while three demonstrated high risk. Meta-analyses demonstrated a moderate non-significant effect size of 0.5 (95 % CI: −0.8, 1.08; p = 0.08) on depression outcomes, and a small non-significant effect size of 0.12 (95 % CI: −0.1, 0.33; p = 0.23) on anxiety outcomes. The majority of studies lacked sufficient statistical power to detect between-group differences. Following GRADE criteria, confidence in estimates was low. Notwithstanding widespread enthusiasm for co-design, the current evidence base is inadequate to confirm the impact of in-person, co-designed mental health interventions on anxiety and depression. More full-scale evaluation trials of higher quality are urgently needed, along with uniform terminology and measurement.